Field structure in linguistics - Nesif, Yusifli Arzu; Markaz, Jamalzade Khanim; Baylar, Allahverdiyeva Ayshan (Eximia, 2023)
The idea of the field was first put forward in German linguistics, and this interrelated term is widely used in a number of fields of science. This method has been used in linguistics since the beginning of the XX century. However, in linguistics, the opinion was unanimously defended and accepted that not all components of the field work with the same intensity and are not equally significant, and that they, in turn, are divided into central and peripheral layers. There are also various sizes, criteria for determining the central-peripheral division in the linguistic literature. From what has been said about the field structure, it is clear that both functional and semantic fields and purely verbal fields accumulate words, grammatical forms, signs that have the same or similar meaning and help to express, realize shades of meaning.